Odpowiedzi

2010-02-22T13:00:47+01:00
A)2(x+3)-(5-x)+2=3-(x-1)
2x+6-5+x+2 = 3-x+1
x+3=-x+4 /+x -3
2x= 1
x=1/2 (0,5)

b)3(x-4)-2(3-2x)=-(3x-1)-(1-x)
3x-12-6+4x = -3x+1-1+x
7x-18 = -2x /+2x +18
9x = 18 /:2
x = 2

c)2x-(x+4)-1=2-3(1-x)+3x
2x-x-4-1 = 2-3+3x+3x
x-5 = -1 +6x
5x = -4
x = -4/5


d)1-2(x-3)-(3x+5)=-x-(2x-1)+3
1-2x+6-3x-5 = -x-2x+1+3
2-5x = 4-3x
2x = -2
x = -1

e)x/3-x/2=⅚
co jest po znaku "="??

f)x+1/2-x-1/4=1½
x redukują się, równanie niewłaściwe

g)(x-1)²+(2+x)²=(x-3)²+x(x+3)
x²-2x+1+4+4x+x² = x²-6x+9+x²+3x
2x²+2x+5 = 2x²-3x+9
5x = 4
x = 1 i 1/4

h)2x+3=x-5 /-x -3
x = -8

i)x+7=22 /-7
x = 15
1 5 1
2010-02-22T13:24:40+01:00
A)
2(x+3)-(5-x)+2=3-(x-1)
2x+6-5+x+2=3-x+1
2x+x+x=3+1-6+5-2
4x=1
x=¼

b)
3(x-4)-2(3-2x)=-(3x-1)-(1-x)
3x-12-6+4x=-3x+1-1+x
3x+4x+3x-x=1-1+12+6
9x=18
x=2

c)
2x-(x+4)-1=2-3(1-x)+3x
2x-x-4-1=2-3+3x+3x
2x-x-3x-3x=2-3+4+1
-5x=4
x=-⅘

d)
1-2(x-3)-(3x+5)=-x-(2x-1)+3
1-2x+6-3x-5=-x-2x+1+3
-2x-3x+x+2x=1+3-1-6+5
-2x=2
x=-1

e)
x/3-x/2=⅚
2x-3x=⅚
-x=⅚
x=-⅚

f)
x+1/2-x-1/4=1½
x-x=1½-½+¼
0≠1¼

g)
(x-1)²+(2+x)²=(x-3)²+x(x+3)
x²-2x+1+4+4x+x²=x²-6x+9+x²+3x
x²+x²-x²-x²-2x+4x+6x-3x=9-1-4
5x=4
x=⅘

h)
2x+3=x-5
2x-x=-5-3
x=-8

i)
x+7=22
x=22-7
x=15
1 5 1